Nonfouling and Antibacterial Zwitterionic Contact Lenses Loaded with Heme-Mimetic Gallium Porphyrin for Treating Keratitis - Qi, Xiaoyu (Langmuir : the ACS journal of surfaces and colloids, 2022)
Antifouling and antibacterial are two critical challenges in the development of contact lenses (CLs). Herein, we presented nonfouling and antibacterial bifunctionalized CLs by encapsulating cationic heme-mimetic gallium porphyrin (Ga-CHP) into zwitterionic-elastomeric-networked (ZEN) hydrogel. Results proved that the ZEN hydrogel showed excellent abilities to resist non-specific protein adsorption, bacterial adhesion, and biofilm formation. Moreover, Ga-CHP could be sustainably released and kill >99.9% planktonic bacteria and >99.9% mature biofilms. In vivo, the symptoms of bacterial keratitis in mice were significantly alleviated after wearing the CLs for 7 days via iron-blocking and photodynamic synergistic antibacterial therapy with the help of natural sunlight. This study highlights the nonfouling and antibacterial superiority of the Ga-CHP-functional zwitterionic CLs and proposes a portable yet efficient non-antibiotic keratitis treatment strategy